The Influence of Coaching and Motivation-Based Principal Supervision on the Professionalism of Elementary School Teacher Performance - Sri Kusningsih; Beni Habibi; Yoga Prihatin (Universitas Pancasakti Tegal, 2026)
This research is motivated by the fact that the professionalism of elementary school teachers' performance is still not optimal. The purpose of this research is the influence of coaching-based supervision and motivation on the professionalism of teacher performance. The quantitative inferential approach with the survey method Multiple linear regression Population of 100 teachers with a sample of 80 teachers in the Taman District Coordinator area with a purposive sampling technique. The research instrument was tested for validity and reliability. Data collection techniques through questionnaires with a linkert scale, observation and documentation. Data analysis through classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), multiple linear regression, ANOVA, t-test, F-test and determination coefficient (R²). The results of the research showed that the regression coefficient value (X1) B = 0.581 with a t-count value = 8.420 and a significant value (p) < 0.001. The motivation variable (X2) was B = 0.367, with a t-count = 5.773 and a significant value (p) < 0.001. The teacher performance professionalism variable was 94.6% (R² = 0.946%). Simultaneously, the principal's supervision based on coaching and motivation had a significant effect on the professionalism of elementary school teacher performance.